LOCAL ECONOMIC DEVELOPMENT THROUGH WOMEN'S EMPOWERMENT WITH GINGER AND GRASS JELLY CULTIVATION IN KAMPUNG LAWAS MASPATI, SURABAYA - Taufiq Hidayat; Sri Kamariyah; Ika Devy Pramudiana; Kristyan Dwijosusilo (Journal of Governance and Public Administration, 2025)
Women's empowerment in the cultivation of ginger and cincau in Kampung Lawas Maspati, Surabaya, East Java, is an effort to improve the economic and social welfare of the women in the community. This research explores women's empowerment in the cultivation of ginger and cincau in Kampung Lawas Maspati, Surabaya, to enhance their economic and social well-being. Despite the promising initiatives, the women still face various challenges, such as limited access to resources, lack of training, and difficulties in accessing markets and funding. Using a qualitative approach, data were collected through interviews, observations, and document studies to analyze the empowerment efforts undertaken and their impact. The results show a positive impact from training and market access support, but challenges such as infrastructure limitations and program sustainability still need to be addressed. In conclusion, further collaboration between the government, community, and academics is needed to ensure the sustainability of this program. Keywords: Women's Empowermen, Ginger and Cincau Cultivation, Economic Welfare